2021
DOI: 10.18502/ijm.v13i3.6384
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of hypervirulent Klebsiella pneumoniae: a systematic review and meta-analysis

Abstract: Classical (CKp) and hypervirulent (hvKp) Klebsiella pneumoniae are two different circulating pathotypes. The aim of this study was to assess the prevalence, epidemiology and molecular relatedness of hvKps using a systemic review and meta-analysis. The data extracted from Medline, Embase, and Web of Science and finally 14 studies met the eligible criteria. To combine prevalence proportions of all studies, we performed the metaprop command embedded in the Meta package software. Totally, of 1814 K. pneumoniae iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…This highlights the convergence of AMR genes and virulence genes among hospital and community hvKp isolates. Previous studies showed ST23 and ST11 as the predominant STs associated with hvKp infection and the evolution of MDR strains ( 20 ). However, in the present study, only one isolate was ST23, with the iucA , rmpA , and rmpA2 genes without any carbapenem resistance genes.…”
Section: Discussionmentioning
confidence: 91%
“…This highlights the convergence of AMR genes and virulence genes among hospital and community hvKp isolates. Previous studies showed ST23 and ST11 as the predominant STs associated with hvKp infection and the evolution of MDR strains ( 20 ). However, in the present study, only one isolate was ST23, with the iucA , rmpA , and rmpA2 genes without any carbapenem resistance genes.…”
Section: Discussionmentioning
confidence: 91%
“…In a meta-analysis conducted by Sanikhani et al . [ 40 ] the rate of reported hypervirulent K. pneumoniae isolates was determined 21.7% globally which majority of them were from China. In our study, P35 and P38 carried non-conjugative hypervirulence plasmids belonging to repB plasmid replicon type and considered as MDR-hypervirulent strains.…”
Section: Discussionmentioning
confidence: 99%
“…The study identified a significant association between health care-related female reproductive tract infections and a history of miscarriage (18). However, no association was found between HAIs and a history of preterm births (19).…”
Section: Discussionmentioning
confidence: 87%